Five-Year Optical Coherence Tomography in Patients With ST-Segment–Elevation Myocardial Infarction Treated With Bare-Metal Versus Everolimus-Eluting Stents. (October 2016) - Gomez-Lara, Josep; Brugaletta, Salvatore; Jacobi, Francisco; Ortega-Paz, Luis; Ñato, Marcos; Roura, Gerard; Romaguera, Rafael; Ferreiro, Jose-Luis; Teruel, Luis; Gracida, Montserrat; Martin-Yuste, Victoria; Freixa, Xavier; et al.
Abstract : Background—: The main causes of late (>1 month) stent thrombosis (ST) are stent uncoverage, malapposition, and neoatherosclerosis. First-generation drug-eluting stents were associated with higher rate of late ST compared with bare-metal stents (BMS), especially in patients with ST-segment–elevation myocardial infarction. Second-generation everolimus-eluting stents (EES) have shown similar rate of late ST than BMS. The aims of the study are to compare the ratio of uncovered to total struts per cross-section ≥30% and other optical coherence tomographic findings associated with ST between EES and BMS in patients with ST-segment–elevation myocardial infarction at 5 years. Methods and Results—: One hundred and sixty-nine consecutive event-free patients of the randomized EXAMINATION study (A Clinical Evaluation of Everolimus Eluting Coronary Stents in the Treatment of Patients With ST-Segment Elevation Myocardial Infarction) were screened for optical coherence tomographic imaging at 5 years. Patients with target vessel–related events or life-threatening comorbidities were excluded. Finally, 64 patients (32 EES and 32 BMS) underwent optical coherence tomographic imaging. At 5 years, uncovered struts (4.1% versus 1.0%; P <0.01), length of uncoverage (3.4 versus 1.4 mm; P =0.02), and ratio of uncovered to total struts per cross-section ≥30% (35.5% versus 9.7%; P =0.02) were larger with EES than that with BMS. Malapposed struts (1.2% versus 0.3%; P =0.02) and malapposition length (1.3 versus 0.4 mm; P =0.06) were also larger with EES. Neoatherosclerotic plaques (16.1% versus 25.8%; P =0.35) and macrophage accumulations (19.4% versus 48.4%; P =0.02) were numerically more frequent with BMS. Conclusions—: Despite substantial dropout of patients, the healing pattern in event-free ST-segment–elevation myocardial infarction patients differs between EES and BMS at 5 years. EES presented with larger amount of uncovered and malapposed struts and similar rate of neoatherosclerosis as compared with BMS. The clinical relevance of these findings warrants longer follow-up. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00828087. Abstract : Supplemental Digital Content is available in the text.